2019
DOI: 10.3390/ijgi8020052
|View full text |Cite
|
Sign up to set email alerts
|

Examining Trade-Offs between Social, Psychological, and Energy Potential of Urban Form

Abstract: Urban planners are often challenged with the task of developing design solutions which must meet multiple, and often contradictory, criteria. In this paper, we investigated the trade-offs between social, psychological, and energy potential of the fundamental elements of urban form: the street network and the building massing. Since formal methods to evaluate urban form from the psychological and social point of view are not readily available, we developed a methodological framework to quantify these criteria a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The need to collect information regarding the effects of activity has been mentioned in a few studies (Birenboim et al , 2019; Kyriakou et al , 2019; Werner et al , 2019). A recent study (Bielik et al , 2019), which compared physiological responses collected in the urban environment with responses collected during replications of the same walk in a controlled virtual reality setting, showed that the physiological arousal elicited from just viewing the urban form was lower than the same experience in the field. Some studies also reported a gradual increase of EDA along the route (Birenboim et al , 2019; Fathullah and Willis, 2018; Griego et al , 2017; Osborne and Jones, 2017), and physical exertion might have played a role there.…”
Section: Critical Reflectionmentioning
confidence: 99%
“…The need to collect information regarding the effects of activity has been mentioned in a few studies (Birenboim et al , 2019; Kyriakou et al , 2019; Werner et al , 2019). A recent study (Bielik et al , 2019), which compared physiological responses collected in the urban environment with responses collected during replications of the same walk in a controlled virtual reality setting, showed that the physiological arousal elicited from just viewing the urban form was lower than the same experience in the field. Some studies also reported a gradual increase of EDA along the route (Birenboim et al , 2019; Fathullah and Willis, 2018; Griego et al , 2017; Osborne and Jones, 2017), and physical exertion might have played a role there.…”
Section: Critical Reflectionmentioning
confidence: 99%
“…Ambience modelling depends on the context and purpose of the study. In some studies, grey-scaled geometries are sufficient; e.g., when examining effects of geometry in isolation of other variables [14,15]. However, in studies that involve experiential measures, ambience or atmospheric cues are more important [8].…”
Section: Achieving Correspondence Between Real and Virtual Environmentsmentioning
confidence: 99%
“…Wellbeing. Five issue papers focused on another aspect of urban human wellbeing: comfort [53][54][55] and crime [56,57]. The former contributions focused on sentiment analysis; the latter two used spatial and machine learning methods, respectively.…”
Section: The Contributions Of This Special Issuementioning
confidence: 99%
“…Nouman et al [54] prototyped a mobile environmental sensor toolkit to asses outdoor comfort using data mining and sensing techniques. Bielik et al [55] performed an empirical study to assess trade-offs in a variety of urban design parameters-social, psychological, and energetic-on planning the fundamental elements of urban form: the street network and the building massing. Concerning crime, Xiao et al [56] analyzed the travel patterns of residential burglars in a Chinese city, disentangling origin and destination effects, while Lin et al [57] explored different machine learning algorithms demonstrating the importance of geographic feature design for improving performance and explanatory ability in grid-based crime prediction.…”
Section: The Contributions Of This Special Issuementioning
confidence: 99%